Evolutionary Approach to the Design and Management of The Production in Supply Net - Ławrynowicz, Anna (Advanced Information Technologies for Management – AITM 2008, 2008)
This paper presents a survey of literature on genetic algorithms in solving optimization problems. The focus is brought on problems related to the design, organization, and management of the supply net. From the recent published literature, the author has identified the following types of problems as the most addressed: cellular organization, facility layout, and optimization of the work- shop configuration, choice of locations for distributions centres, production planning and scheduling, assembly planning, and configuration of the supply net.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 116-125